The Cowichan Tribes early childhood education child and youth care career ladder project - Malaspina University-College (Electronic version published by Vancouver Island University, 1994)
The Cowichan Tribes ECE/CYC Career Ladder represents a successful amalgamation of two cultures and two value systems. The Career Ladder combines the credentials, education and respect that come from a university-recognized, college-credited, postsecondary program in the cultura.lly and socially valued field of child and youth care with traditional Cowichan Tribes child care values through innovative bi-cultural instruction. A renewed appreciation of First Nations values and heritage now exists for students and faculty, and for the Cowichan Tribes and Malaspina University-College communities. Malaspina University-College hopes that this new approach to education, involving a bicultural generative curriculum model and having Elders instruct students will lead its efforts in cross-cultural educational programming. https://viurrspace.ca/bitstream/handle/10613/7582/Career.pdf?sequence=3&isAllowed=y